Aufstockung des äthiopischen Handschriftenbestandes zweier deutscher Bibliotheken - Six, Veronika (Aethiopica, 2009)
Two German libraries which hold collections of Oriental manuscripts again have enlarged their stock of Ethiopian manuscripts. The Berlin State Library: there is a dated Sǝnkǝssar representing the still living manuscript tradition. Without concrete dating (which exists) a cataloguer surely might come to a wrong judgment concerning the date of writing the manuscript, but the date is clear: 20th cent. The second manuscript is a gift from Professor Dr. Walter W. Müller (Marburg): the unbound parchment leaves contain chronicles in Amharic concerning the history of Ethiopia and Šäwa written in the second half of the 19th cent. Then a collection of Hymns (Sälam), a Psalter and a small manuscript containing a text which is used as protection of the soul either during funeral rites or – as it is the case here – as a separate text serving the daily protection of a human being. The second library: the University Library Tübingen with a long tradition of collecting Oriental and Ethiopic manuscripts as well, now has acquired two manuscripts: a dated Mäzmurä Dawit of the second half of the 19th cent. which also represents the manuscript tradition at its best and a parchment scroll containing prayers for protecting a female person, but in which the originally restricted purpose has been changed into a general protective function.